THE PROTECTION OF CHILDREN DURING ARMED CONFLICTS: ISRAELI VIOLATIONS OF INTERNATIONAL HUMANITARIAN LAW IN THREE WARS IN GAZA (UUM Journal of Legal Studies, 2023)
Children are one of the most vulnerable categories of victims during armed conflicts. Although several international instruments exist to protect them and civilians in general, there are still many violations committed against children worldwide. This article reports a pure doctrinal research that has used a descriptive analytical approach. It seeks to address the issue of the protection of children from the perspective of International Humanitarian Law. The context of the study is its focus on Israeli violations committed during three wars in the Gaza Strip, i.e., in 2008, 2012 and 2014. The violations were analysed using the framework of the rules and principles ofInternational Humanitarian Law, specifically the Geneva Convention IV and its two additional protocols regarding the protection of children during armed conflicts. It is important to understand the nature of the protection provided to children under International Humanitarian Law and to identify whether the Israeli forces breached the rules during the three wars. This will expose the Israeli violations and provide better protection for the people in Gaza, especially children in wartime. Finally, the study summarises that the International Humanitarian Law provides a special protection to children in wartime alongside the protection provided to civilians. It also concludes that during the wars in the Gaza Strip, i.e., in 2008, 2012 and 2014, Israel did violate the principles of International Humanitarian Law concerning children and the civilians in general.